Resource base for the development of geothermal energy in Ukraine - Shurchkova Yu.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The article presents materials on the state of geothermal resources and the possibility of their extraction in Ukraine. The types of classification of geothermal resources are considered. The data of geological studies of the temperature fields of rocks at depths from 0 to 10 km, as well as data on thermal waters and their reserves to a depth of 5 km are presented. The possibility of using existing wells in oil and gas fields for the extraction of geothermal waters is considered. The conclusion provides data on the regions of Ukraine that are promising for the development of geothermal energy.The world leaders in the use of geothermal energy are countries located in the field of modern volcanism, where the heat carrier has high parameters, is accessible on the Earth's surface, the cost of constructing geothermal facilities is minimal, and the cost of energy is competitive in the energy market. Ukraine does not belong to the list of these countries. Cost-efficient high-potential resources are distributed in few regions, which, in addition, were examined insufficiently. Low potential resources are available almost everywhere, but require either expensive deep drilling, or large areas for shallow wells. The most promising regions are those in which the highest temperatures of rocks are observed at accessible depths, and there are highly depleted aquifers such as Transcarpathia, Stepnoy Crimea, and the Kerch Peninsula. Hewever, taking into account the fact that a series of regions, in particular, the Dnieper-Donets Basin, was poorly studied for the development of geothermal energy supply, and also with regard for the capabilities of modern technologies for the transformation of low-grade heat, the list of promising areas can be significantly expanded.Numerous allegations in the literature about the huge reserves of geothermal energy in Ukraine, about the capacity of hypothetical geothermal power plants do not always seem reasonable. An assessment of geothermal resources without a preliminary comprehensive study of the field, trial drilling, or studying the properties of aquifers may be not accurate. Therefore, it seems premature to talk about the possibility of creating large geothermal power plants at the present stage. Along with the rapidly developing construction of solar and wind power plants, geothermal energy can take its rightful place in hydrothermal heat supply.